2023
DOI: 10.1002/ajmg.a.63214
|View full text |Cite
|
Sign up to set email alerts
|

Novel mosaic TRAF7 likely pathogenic variant in an African American family

Abstract: Pathogenic variants in TRAF7 are often de novo and features of individuals harboring these variants are characterized by neurodevelopmental delay, ptosis, cardiac defects, limb anomalies, and dysmorphic features. We present a familial case in two African American patients with a novel, likely pathogenic c.1936G>A variant in TRAF7. Patient 1 is a 31-year-old female with a patent ductus arteriosus (PDA), intellectual disability, ptosis, and other dysmorphic features. She was identified to harbor this likely path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The absence of PDA in our cases is likely due partly to the documented exclusion of probands with isolated PDA from the Pediatric Cardiac Genomics Consortium (PCGC) cohort, which focuses on severe CHD. Nonetheless, our three probands show phenotypic overlap with previous reports (atrial septal defects, pulmonary atresia, and ventricular hypoplasia) ( 2 , 4 ), including polydactyly ( 8 , 9 ). Minimal phenotyping of parents in PCGC limits any further phenotypic correlations, including possible incomplete penetrance ( 2 ).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The absence of PDA in our cases is likely due partly to the documented exclusion of probands with isolated PDA from the Pediatric Cardiac Genomics Consortium (PCGC) cohort, which focuses on severe CHD. Nonetheless, our three probands show phenotypic overlap with previous reports (atrial septal defects, pulmonary atresia, and ventricular hypoplasia) ( 2 , 4 ), including polydactyly ( 8 , 9 ). Minimal phenotyping of parents in PCGC limits any further phenotypic correlations, including possible incomplete penetrance ( 2 ).…”
supporting
confidence: 54%
“…Gordon et al themselves report only one child presenting the CHD phenotype ( 3 ) in a family of a mother with dizygotic twins carrying p.Phe617Leu mutation. Similarly, a p.Val646Ile mutation presents differently in a mother and son, with only the mother displaying polydactyly and dysmorphic facial features ( 9 ). Moreover, phenotypes of probands with identical missense mutation documented substantial variability of cardiac phenotypes ( 4 ), supporting variable expressivity of TRAF7 mutations.…”
mentioning
confidence: 99%
“…TRAF7 syndrome (also known as CAFDADD; Cardiac, facial, and digital anomalies with developmental delay; MIM #618164; ORPHA: 592570) is a multisystemic neurodevelopmental disorder caused by heterozygous germline pathogenic variants in the TRAF7 gene (Tumor necrosis factor receptor-associated factor 7; MIM *606692). Since its initial description in 2018 [1] and further delineation [2], a total of 58 subjects with TRAF7 syndrome have been published, carrying 26 different variants [38]. While the clinical presentation of the syndrome appears to be highly variable, some common features have been identified, including a range of neurological and developmental abnormalities, such as intellectual disability, speech and language delays, and motor impairments, as well as epilepsy in some individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial description in 2018 [1] and further delineation [2], a total of 58 subjects with TRAF7 syndrome have been published, carrying 26 different variants [3][4][5][6][7][8]. While the clinical presentation of the syndrome appears to be highly variable, some common features have been identified, including a range of neurological and developmental abnormalities, such as intellectual disability, speech and language delays, and motor impairments, as well as epilepsy in some individuals.…”
Section: Introductionmentioning
confidence: 99%
“… Only anomalies affecting the four chambers and great arteries are listed. Full details of references can be found in the main text, plus: Colleran et al ( 8 ). Although Castilla-Vallmanya et al, identified TRAF7 variants in 45 patients, N = 42 refers to the core cohort of patients harboring variants in the WD40 repeats.…”
mentioning
confidence: 99%